2006
DOI: 10.1524/ract.2006.94.9-11.489
|View full text |Cite
|
Sign up to set email alerts
|

Solubility measurement of zirconium(IV) hydrous oxide

Abstract: The solubility of zirconium(IV) hydrous oxide was measured in the hydrogen ion concentration (pH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 13 publications
7
49
3
Order By: Relevance
“…2,3) In our recent study, for example, the solubility of zirconium hydrous oxide was investigated by considering the presence of colloidal species. 4,5) The formation of polynuclear and colloidal species, of which a steady-state size distribution was reached within a few months, was observed in oversaturation experiments. From the size distributions of the apparent solubility data, it was found that mononuclear, polynuclear and colloidal species under 3 kDa in size might be present, even in acidic solution.…”
Section: Introductionmentioning
confidence: 99%
“…2,3) In our recent study, for example, the solubility of zirconium hydrous oxide was investigated by considering the presence of colloidal species. 4,5) The formation of polynuclear and colloidal species, of which a steady-state size distribution was reached within a few months, was observed in oversaturation experiments. From the size distributions of the apparent solubility data, it was found that mononuclear, polynuclear and colloidal species under 3 kDa in size might be present, even in acidic solution.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the mononuclear species of Th 4þ , ThOH 3þ , Th(OH) 2 2þ , Th(OH) 3 þ , and Th(OH) 4 (aq) were treated inclusively as a monomeric unit in the model similarly to our previous study on the Zr hydrolysis species. 14) The total number, Nðl 1 ; l 2 Þ, of monomeric units comprising the chain molecules in the range l 1 to l 2 in size is given by…”
Section: Resultsmentioning
confidence: 99%
“…Immediately after the preparation of the solution, the hydrolysis reaction and polymerization process began, depending on the pH and the aging period. 7) Samples aged for 3 months were used for measurements unless otherwise stated. The spectrum of the samples aged at pH c > 3 could not be obtained due to the low Zr solubility.…”
Section: Methodsmentioning
confidence: 99%
“…7,8) For instance, the formations of polynuclear and colloidal species, for which a steady state size distribution was reached after a few months, were observed in oversaturation experiments. 7) From the observed size distributions, it was found that 3 kDa mononuclear, polynuclear, and colloidal species (Microcon Centrifugal Filter, Millipore) might exist even in an acidic solution. It is interesting to note that further polymerization would occur very slowly after reaching a nearly steady state in 3 months.…”
Section: Sample Aging For Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation